2020
DOI: 10.1007/978-3-030-41057-5_46
|View full text |Cite
|
Sign up to set email alerts
|

Bond Behavior of TRM Systems and Reinforcement of Masonry Arches: Testing and Modelling

Abstract: The paper addresses the results of experimental and analytical investigations on composite systems able to reduce structural vulnerability of arches. Two composites, consisting of a PBO (propylbenzodioxole) fibre textile or a carbon fibre textile coupled with a cement-based matrix, are considered. Experimental results on bond capacity between composites and bricks and on the structural behaviour of unreinforced and extrados-reinforced 1:2 scale masonry arches, tested under vertical load, are presented. The glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…TRM by Misseri et al [33]. They found that the CFRP reinforced arches had a strength 10 times higher than the unreinforced arches whereas that the PBO TRM reinforced arches achieved a strength increment of 5 times.…”
Section: Experimental Campaignsmentioning
confidence: 98%
“…TRM by Misseri et al [33]. They found that the CFRP reinforced arches had a strength 10 times higher than the unreinforced arches whereas that the PBO TRM reinforced arches achieved a strength increment of 5 times.…”
Section: Experimental Campaignsmentioning
confidence: 98%
“…First developed as fibre reinforced polymers (FRP) in other branches of applied technologies, lately, they have been introduced in the construction field (Kouris and Triantafillou, 2018;Gattesco and Boem, 2019). To overcome some significant drawbacks caused by the organic binder of FRP matrices -namely low resistance to high temperature, low vapour permeability and failure by delamination from the substrate, fibre reinforced cementitious mortars (FRCM) have been developed using loose mesh textiles and cement or lime-based mortars (Briccoli Bati et al, 2007;Rovero et al, 2013;Rotunno et al, 2015;Alecci et al, 2016;Misseri et al, 2019aMisseri et al, , 2019bKumar et al, 2019;Barducci et al, 2020;Misseri et al, 2020;Padalu et al, 2020;Boem and Gattesco, 2021), which ensure better compatibility with the masonry substrate. Gypsum based mortars proved also effective (Rovero et al, 2020;Misseri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%